Analysis and Design Pet Healthcare, Pet Adoption, and Pet Community iOS Mobile Application for Animal Lovers - Darmawan, Dion; Khresna, Roberto (Bina Nusantara University, 2025)
This research aims to create an iOS based mobile applications that is expected to assist pet owners who want to search for reliable caretaker for their pets, ensuring a safe and trustworthy environment for pet entrustment. The application will also serve as an extensive informational hub, providing users with valuable resouces, including articles about pet and directory of veterinary clinics around the user’s area. The development of this mobile application begins with data collection through, literature study, observation and questionnaire. Literature study aims to find supporting theories which can assist the development of this application, observation are made to compare the application to be developed with similar applications, and questionnaire is used to identify the requirement from potential users. After analyzing all the obtained data, the process continues with designing application systems with UML diagrams such as, use case diagram, use case descripton, class diagram, sequence diagram, and activity diagram. Then, after completing the system design phase, the development of the application will be carried out with kanban methodology. After the application has been developed, a survey will be distributed to potential users to asses their level of satisfaction with the developed application. This survey will aim to gather feedback on various aspects, including user experience, functionality, ease of navigation, and overall effectiveness in meeting user needs.